Minoritetspolitiske dokumentasjonsstrategier i Nordområdet på 1700-tallet - Lindbach, Harald Haraldsen (UiT Norges arktiske universitet, 2020)
Minoritetspolitiske dokumentasjonsstrategier i Nordområdet på 1700-tallet. En komparativ analyse av hvordan og hvor samer og kvener trer frem i arkivene til lokal- og regionalforvaltningen i Danmark-Norge og Sverige, med spesielt blikk på Nord-Troms, Jukkasjärvi og Enontekis. Justisprotokoller, domsbøker og misjonsarkiver og kirkelige arkiver blir spesielt belyst i avhandlingen. The thesis examines how and where minorities and indigenous people, Kven and Saami, appear in the archives of local and regional administrations in the states of Denmark-Norway and Sweden in the 18th century. Although minorities often are hidden in the archives of the states, at both local and regional level, it is possible to find important documents that give insight into the lives and histories of indigenous peoples and minorities in the 1700s. However, the finding aids that are developed for archival search do not provide good enough results and other methods will have to be used.